ASSESSMENT OF IMPACT BY PHYSICAL AND MECHANICAL PARAMETERS OF THE FILLER ON DYNAMIC BEHAVIOUR OF THE CYLINDRICAL SHELL - HUD, MYKHAILO; VOROSHCHUK, VIKTOR; OLEKSIUK, VASYL; HAHALIUK, ANDRII (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The article presents the results of numerical modelling of the influence of physical and mechanical characteristics of the filler on the dynamic behaviour of a thin-walled reinforced cylindrical shell, specifically on its natural vibration rates. Shell structures are widely used in various industries, including aviation, space engineering, transport systems, and agriculture, where reliability and resistance to dynamic loads are critical. One of the determining factors for the safe operation of such structures is the identification of frequency resonance zones, especially in the presence of internal fillers with different densities and stiffnesses. If the natural frequencies of the shell coincide with the vibrations of external disturbances or system components, critical overloads and premature failure may occur.In this work, a modal analysis was carried out using the finite element method in the ANSYS APDL environment, which allowed us to obtain the dependence of the natural vibration frequencies on the density (ρ) and elastic modulus (E) of the filler material. Several characteristic combinations of density ρ (100, 160, 220 kg/m³) and elastic modulus E (1, 3, 6 MPa) were considered, which allowed for a broad analysis of the influence of mass and stiffness parameters on the shell behaviour. The model takes into account structural features such as the presence of stringers and frames that ensure the rigidity and geometric stability of the cylinder. Computational elements such as SHELL181 and BEAM188, as well as the use of the Lanzosh block method to determine the modal characteristics, ensured high accuracy of the calculations.The results of the study showed that with a decrease in the filler density at a constant elastic modulus, the natural frequencies increase significantly. This is due to a decrease in the inertial load, which gives the system greater dynamic stiffness. On the other hand, an increase in density causes inertial braking and an overall decrease in frequencies, which is especially noticeable at lower modes. Similarly, an increase in the modulus of elasticity at a constant density leads to a significant increase in vibration frequencies, which is due to an increase in the stiffness of the structure and its ability to resist deformation. At a minimum value of the elastic modulus (1 MPa), a significant number of modes with zero frequencies are observed, indicating a loss of dynamic stability.The constructed frequency graphs for various combinations of filler parameters allow us to visually track dynamic changes and provide grounds for formulating practical recommendations for the selection of fillers in structures operating under vibration loading. The results obtained are important for ensuring the reliability and durability of shell structures in various fields of engineering, including transport, energy, and industrial construction.
Keywords: shell; oscillations; experiment; research